A self-generated and degradation-resistive cratered stainless steel electrocatalyst for efficient water oxidation in a neutral electrolyte. Issue 36 (31st August 2017) - Lee, Minoh; Jeon, Hyo Sang; Lee, Si Young; Kim, Haeri; Sim, Sang Jun; Hwang, Yun Jeong; Min, Byoung Koun
Abstract : The chemical composition change of Ni and Fe on a cratered stainless steel surface as a result of electrochemical oxidation leads to significantly enhanced water oxidation properties in a neutral electrolyte. Abstract : An electron-mediated CO2 -to-chemical conversion system is regarded as one of the effective solutions for the depletion of fossil fuels and the accumulation of atmospheric CO2 . In this process, the protons and electrons generated from the water-oxidation reaction at an anode are used during the reduction of CO2 at a cathode, in order to produce high-value hydrocarbon chemicals. Therefore, water oxidation is also a key reaction for the overall electron-mediated CO2 -to-chemical conversion. In this work, a facile preparation method is developed for a highly efficient water oxidation electrocatalyst which stably operates in a neutral bicarbonate electrolyte optimized for CO2 -reduction conditions. Ni-rich cratered structures were spontaneously formed on the stainless steel surface by harsh electro-oxidation, and the chemical composition changes of Fe and Ni on the catalyst surface dramatically enhance water-oxidation activity showing an overpotential value of 504 mV at 10 mA cm −2 in a CO2 -saturated bicarbonate electrolyte. In contrast to a severe degradation in the phosphate electrolyte, the cratered stainless-steel (CSS) catalyst is very stable for an 18 h reaction in the bicarbonate electrolyte. Surface spectroscopic analyses of CSS consistently revealed that the active-surface structure of the NiOOH and adsorbed water molecules is remarkably stable throughout water-oxidation in the neutral bicarbonate electrolyte, while the destruction of Ni structures by the phosphate electrolyte is proposed to cause concomitant activity loss for water oxidation.